Circulating prostaglandin E2 concentrations decrease at birth in premature lambs - Panneflek, Timothy J. R.; Dekker, Janneke; Crossley, Kelly J.; Diedericks, Cailin; Kuypers, Kristel L. A. M.; Cannata, Ebony R.; Riddington, Paige J.; Bloem, Femmie E.; Thiel, Alison M.; van den Akker, Thomas; Polglase, Graeme R.; te Pas, Arjan B.; et al. (Frontiers in Pediatrics, 2025)
RationaleDuring pregnancy, prostaglandin E2 (PGE2) is released from the placenta and circulates in relatively high concentrations in the fetus. As PGE2 suppresses breathing, PGE2 concentrations must decrease after birth, but the timing and mechanisms behind this decrease are unknown. We hypothesised that both umbilical cord clamping and lung aeration contribute to the reduction in PGE2 concentrations after birth.Materials and methodsInstrumented premature lambs (138–141 days gestation) were randomised to receive either physiological-based cord clamping (PBCC; cord clamping after ventilation onset; n = 5) or immediate cord clamping (ICC; before ventilation onset; n = 6). PGE2 concentrations were measured in pulmonary and carotid arterial blood 30 s after ventilation onset, after lung aeration and 30 s after cord clamping. All PGE2 data are expressed relative to fetal PGE2 concentrations.ResultsRelative to fetal concentrations, ventilation onset decreased PGE2 concentrations in the carotid (p = 0.036) and pulmonary arteries (p = 0.052) in PBCC lambs, whereas cord clamping had no further additional effect on PGE2 concentrations in these lambs. In ICC lambs, cord clamping decreased PGE2 concentrations, relative to fetal concentrations, in both the carotid (p = 0.001) and pulmonary arteries (p < 0.001). Ventilation onset further decreased PGE2 concentrations in both the carotid (p = 0.002) and pulmonary arteries (p = 0.014).ConclusionBoth umbilical cord clamping and ventilation onset independently decrease PGE2 concentrations immediately after birth, which may enhance breathing activity, although the effect of cord clamping is reduced by ventilation onset.